2021
DOI: 10.1007/s10578-021-01280-w
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Associations Between Cannabis Use and Anxiety in Adolescents and Young Adults

Abstract: Cannabis and anxiety are both rising issues that impact young people. This review seeks to explore the association between anxiety and cannabis in adolescents and young adults (AYA). A database search was run retrospectively from July 2020 through calendar year 2013. Articles had to present outcomes examining cannabis use and symptoms of anxiety, be written in English, contain samples with ≥ 50% who are age 25 or younger, and be published in a peer-reviewed journal. Forty-seven studies were identified that exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The pathophysiology by which this plant causes an anxiogenic effect in some individuals is poorly understood. Still, given that cannabis contains over 400 different chemical compounds, including 100 different cannabinoids, the pathology is likely to involve multiple pathways [18][19]. Teenagers and young children, whose brains are still developing, are particularly vulnerable to marijuana's neuropsychiatric effects [8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology by which this plant causes an anxiogenic effect in some individuals is poorly understood. Still, given that cannabis contains over 400 different chemical compounds, including 100 different cannabinoids, the pathology is likely to involve multiple pathways [18][19]. Teenagers and young children, whose brains are still developing, are particularly vulnerable to marijuana's neuropsychiatric effects [8][9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that subjects in self-isolation due to COVID-19 tend to use 20% more cannabis compared to those who did not [43]. Moreover, social anxiety has been associated with frequent cannabis use [44] that evokes several neuroadaptations in the ECS [45].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, cannabis use has been linked to various harms, including increased risk of depression ( Gobbi et al, 2019 ), anxiety ( Stiles-Shields et al, 2021 ), suicidal ideation and attempts ( Gobbi et al, 2019 ), and psychosis ( Hall & Degenhardt, 2008 ). The risks associated with cannabis use may be especially heightened for postsecondary students, as emerging adulthood is recognized as a critical developmental period during which individuals may be particularly susceptible to the consequences of substance use ( Stone et al, 2012 ).…”
mentioning
confidence: 99%